Algorithmic Hotness: Young Women’s “Promotion” and “Reconnaissance” Work via Social Media Body Images - Carah, N.; Dobson, Amy (2016)
This article examines how the circulation of images on mobile and algorithmic social media platforms is gendered. We draw on data from a research project that examines the interplay between promotion, drinking culture, and social media. In this project, informants documented flows of images between their social media accounts and a nightlife precinct. We show how the human capacity to use bodies to affect other bodies, and to make critical judgments about bodies, is vital to algorithmic media platforms that aim to profit from calculative judgements about the affective dimensions of human life. We propose an expanded register of “body heat” on social media as both the symbolic labor of producing, maintaining, and digitally mediating a body that conforms to heterosexy visual codes and the affective labor of using a hot body to affect other bodies through movement, touch, and excessive consumption. The escalating capacity of social media platforms to calibrate flows of attention depends on the “hot” bodies of users and user’s work in curating “hot” body images to upload. Hot female bodies are critical to nightlife promotion via social media, in attracting viewer attention. Hot female bodies are also key to moments of nightlife reconnaissance: they are registered in the databases and sorted by the algorithms of social media platforms, enabling viewers to make judgments about the desirability of locations in the nightlife precinct.